The role of capital in microfinance financial performance and cultural sustainability - I Wayan Pradnyantha Wirasedana; Made Sudarma; Wuryan Andayani; Aji Dedi Mulawarman (Cogent Business & Management, 2024)
This study seeks to understand the role of intellectual capital and capital structure in maintaining the financial performance and cultural sustainability of village credit unions in Bali, locally known as lembaga perkreditan desa (LPD), which is crucial in the funding of cultural and religious activities of traditional villages. Intellectual capital is measured using value-added intellectual capital coefficient (VAIC) and partially analysed by human capital, structural capital, and capital employed efficiency. This study uses panel data samples of 307 LPD representing all nine regencies in Bali from 2020 to 2022. The analysis was performed using multiple linear regression, with findings that intellectual capital has a positive impact on financial performance and cultural sustainability, while capital structure shows insignificant impact. Furthermore, the control variables suggest that age and financial health have a positive impact on financial performance, whereas size has an insignificant impact. The results suggest that the LPD would need to improve its intellectual capital efficiency to achieve the desired financial performance and maintaining the cultural sustainability of the traditional village. It implicates that intellectual capital within its intangible nature has more impact than inherent practices of capital composition associated with microfinance.
Keywords: G21; M41; 650; Intellectual capital; capital structure; financial performance; cultural sustainability; microfinance